Brucelosis porcina - Ortez Sarantes, Efren (Estelí (Nicaragua), 1978)
Sumario (Es)
3 ref.
Tesis (Tec Agr)
Keywords: ANIMALES DOMESTICOS; ENFERMEDADES INFECCIOSAS; ENFERMEDADES DE LOS ANIMALES; BRUCELOSIS; NICARAGUA